A process for increasing plastic strain ratio of AA1050 Al alloy sheet. (2017) - Kim, Gwang-Hee; Nam, Su Kwon; Lee, Dong Nyung; Kim, Insoo
The process of heavy asymmetric rolling (90%) and annealing, followed by light rolling (10%-25%) and annealing has been known to improve the plastic strain ratios (the R-values) of AA1050 Al alloy sheets. The thickness of 90% asymmetrically rolled sheet is so thin that it is difficult to control the light rolling reduction. In order to better control the light rolling reduction, the heavy asymmetric rolling reduction was reduced to 60% in this study. The Al alloy sheets processed by the heavy asymmetric rolling (60%) and annealing, followed by light rolling (10%-25%) and annealing were subjected to the texture measurement. The R-values of the sheets were calculated from the measured sheet textures using the Bunge method. AA1050 Al alloy sheets processed by the 60% heavy asymmetric rolling and annealing for 1 h at 400°C, followed by 15% light rolling and annealing for 1 h at 400°C had an average R-value of 1.05, which is about 1.86 times higher than that of the initial sample.